CXCL8, CXCL9, CXCL10, and CXCL11 as biomarkers of liver injury caused by chronic hepatitis B - Yu, Xin; Chen, Ying; Cui, Lele; Yang, Kaming; Wang, Xumeng; Lei, Linyuan; Zhang, Yanping; Kong, Xinyi; Lao, Wanwen; Li, Zhenlin; Liu, Yang; Li, Yuetong; et al. (Frontiers in Microbiology, 2022)
Chronic hepatitis B (CHB) remains a significant global health problem, leading to recurrent inflammation and liver-damaging diseases such as fibrosis, cirrhosis, and hepatocellular carcinoma (HCC). Currently, although diagnostic markers for CHB are well established, the indicators for predicting liver injury caused by hepatitis B virus (HBV) infection still need to be further explored. Thus, the identification of credible infectious indicators is urgently needed to facilitate timely clinical intervention and avoid the progression of disease malignancy. To find relevant markers, the GEO database GSE83148 data set was used to analyze the differentially expressed genes between HBV-infected persons and healthy tissue samples. Four hub genes were identified: chemokine (C-X-C motif) ligand (CXCL)8, CXCL9, CXCL10, and CXCL11. The qPCR results demonstrated that the expression of these four chemokines were remarkably increased after HBV infection. The ELISA results showed that the concentrations of serum CXCL8, CXCL9, CXCL10, and CXCL11 were also raised after HBV infection. Correlation analysis was used to confirm that the four chemokines were significantly positively correlated with AST, and ALT. Finally, CXCL9, CXCL10 and CXCL11 were found to be significantly upregulated in normal tissues compared with HCC tissues via the GEPIA database. Using a combination of bioinformatics, cell experiments, and clinical correlation analysis, this study showed that CXCL8, CXCL9, CXCL10, and CXCL11 can be used as serum biomarkers to forecast liver injury caused by HBV infection.